Cannabinoid Receptor Type 1 regulates growth cone filopodia and axon dispersion in the optic tract of Xenopus laevis tadpoles. (2nd February 2022) - Elul, Tamira; Lim, John; Hanton, Kenneth; Lui, Austin; Jones, Kenton; Chen, George; Chong, Celeste; Dao, Sophia; Rawat, Radhika
Abstract: Previous studies show that the main cannabinoid receptor in the brain—cannabinoid type 1 receptor (CB1R)—is required for establishment of axonal projections in developing neurons but questions remain regarding the cellular and molecular mechanisms, especially in neurons developing in their native environment. We assessed the effects of CB1R signalling on growth cone filopodia and axonal projections of retinal ganglion cells (RGCs) in whole mount brains from Xenopus laevis tadpoles. Our results indicate that growth cones of RGC axons in brains from tadpoles exposed to a CB1R agonist had fewer filopodial protrusions, whereas growth cones from tadpoles exposed to a CB1R inverse agonist had more filopodia than growth cones of RGC axons in whole brains from control tadpoles. However, application of both the CB1R agonist and inverse agonist resulted in RGC axons that were overly dispersed and undulatory in the optic tract in situ. In addition, expression of a mutant for cadherin adhesive factor, β‐catenin, that disrupts its binding to α‐catenin, and application of an inhibitor for actin regulator non‐muscle Myosin II, phenocopied the effects of the CB1R agonist and inverse agonist on growth cone filopodia, respectively. These findings suggest that both destablization and stabilization of growth cone filopodia are required for RGC axonal fasciculation/defasciculation in the optic tract and that CB1R regulates growth cone filopodia and axon dispersion of RGCs by oppositely modulating β‐catenin adhesive and Myosin II actin regulatory functions. This study extends and confirms our understanding of cannabinoid mechanisms in sculpting developing neuronal circuits in vivo. Abstract : Growth cones exposed to CB1R agonist had fewer filopodial protrusions, whereas those exposed to CB1R inverse agonist had more filopodial protrusions than controls. A β‐catenin mutant induced the same effects as CBR agonist, while an inhibitor of Myosin II phenocopied the inverse agonist on growth cone filopodia. These results imply that the activation of CB1R results in negative regulation of β‐catenin and positive regulation of Myosin II, which both ultimately leads to fewer filopodia protrusions. By oppositely modulating β‐catenin and Myosin II, CB1R regulates growth cone filopodia and the balance of destabilization/stabilization of the filopodia results in proper axonal defasciculation in the tract.